Motivation Therapy to Pulmonary Tuberculosis Patients in Improving Compliance Consuming Antituberculosis Drugs - Karyo Karyo (Aloha International Journal of Health Advancement (AIJHA), 2021)
Introduction: Puskesmas Semanding, Tuban, East Java, Indonesia became the health center with the largest number of patients with about 40 patients with 35 treated patients and 2 of the rules of resistance or included in the MDR-TB group. Antituberculosis drugs resistance is due to patients not adhering to taking medication. One of the causes was motivation deficit. Methods: This study was to analyze the motivation effect on the Antituberculosis drugs consumption accuracy in TB patients. This a pre-experimental design study. The population was TB patients at the Puskesmas Semanding. The sampling technique was purposive sampling probability with a total of 30 TB patients, taken in line with inclusion criteria. The independent variable is the provision of motivational therapy. The dependent variable is antituberculosis drugs consumption compliance. Instruments for observation were sheets and questionnaires. Data analysis was done using the Chi-Square test with a significance level of 0.05. Results: The study showed that those who adhere to taking medication before therapy was less than 2 persons (6.67%) after therapy was greater than 19 (63.33%). This study showed that motivation has a significant influence on increasing the compliance of TB patients in undergoing Antituberculosis drugs therapy with a value of p=0.00. Conclusions: Based on the results of this study, it is expected that the Puskesmas will be able to provide policies and attention to the importance of motivation in the form of health education and counseling as well as the provision of supervision of taking medication or supervision to succeed in controlling and eradicating TB cases. Keywords: pulmonary tuberculosis; motivation; drug adherence